Effects of blue carbon restoration strategies on sediment carbon sinks and underlying mechanisms across contrasting hydrogeomorphic settings - Jia Lin; Xiaoguang Ouyang; Siqi Nie; Wangli Xing; Yunlin Jiang; Fen Guo; Yuan Zhang; Zhifeng Yang (Water Research, 2026)

Low-temperature plasma priming enhances nutrient removal and astaxanthin production in Haematococcus pluvialis: Transcriptomic responses during controlled aquaculture wastewater cultivation - Zuo Lin; Chen Zhu; Wang Fen; Ha Thanh Dong; Takuji W. Tsusaka; Nimish Devendra Dhuri; Jiang Yelin; Zhou Xiang; Krishna R. Salin (Bioresource Technology, 2026)

Chemical constituents of Paratinospora sagittata and their chemotaxonomic significance - Wei Nie; Zhang-Juan Li; Ye-Ting Shi; Ming Hu; Xing-De Wu; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Chemical constituents from the leaves of Liriodendron chinense and their chemophenetic significance - Qiu-Ye Zhao; Qiu-Hua Wang; Xin-Ying Wang; Lu Sai; Shi-Huan Yin; Dai-Yi Liu; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Discriminative predation stabilizes the fig-fig wasp mutualism in a patch-dynamic framework - Xiao-Fen Lin; Lin Wang; Jin-Bao Liao; Rui-Wu Wang (Ecological Modelling, 2026)

Single-channel magnetotactile interface with structurally decoupled polarity–eigenfrequency encoding for in-plane sliding-direction decoding - Xiaojuan Hou; Shaowei Quan; Xin Zhang; Huipeng Zhao; Lin Shi; Fen Li; Wenping Geng; Jian He; Xiujian Chou (Chemical Engineering Journal, 2026)

Hypurpurins A-P, furanolabdane diterpenoids from the aerial parts of Hypoestes purpurea and their bioactivities - Lin-Fen Ding; Bin Cheng; Mei-Yi Zhang; Shi-Huan Yin; Xin-Ying Wang; Lu Sai; Hui-ling Zhou; Xuan Jiang; Jia Su; Xing-De Wu (Phytochemistry, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

Chemical constituents from the leaves of Yulania denudata and their chemotaxonomic significance - Zhen-Quan Li; Qiu-Ye Zhao; Hui-Ling Zhou; Shi-Huan Yin; Xuan Jiang; Xin-Ying Wang; Lu Sai; Lin-Fen Ding; Liu-Dong Song (Biochemical Systematics and Ecology, 2026)

Immediate effects of binaural beat stimulation on prefrontal cortical activation after cycling exercise: an electroencephalography-based study - Shih-Fen Hsiao; Tzu-Ling Liu; Yu-Chen Lin; Chen-Wen Yen; Ka-Chun Siu; Jau-Hong Lin (Experimental Brain Research, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Integrated multi-matrix bile acid metabolic metrics (BAMMs): A methodological framework for functional metabolic phenotyping in human subjects - Cheng-Hung Yang; Hsiang-Yu Tang; Chun-Ming Fan; Jui-Fen Lin; Mei-Ling Cheng (Analytica Chimica Acta, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Dual-functional isoquercitin‑silver nanoparticles alleviate bacterial-induced excessive inflammation of wound infection and sepsis - Guowei Zhong; Qianfeng Xu; Aidi Tong; Fen Zou; Chunyi Tong; Yangjia Zhuo; Jundong Lin; Wenjie Xie; Jianheng Ye; Jianming Lu; Bin Liu; Huichan He; et al. (Chemical Engineering Journal, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

From gene to function: GABA receptor-associated protein (GABARAP) interacts with and potentiates the GABA receptor (RDL) in Megalurothrips usitatus (Bagnall) (Thysanoptera: Thripidae) - Haifeng Jin; Yonghui Lin; Sumit Singh; Yuran Xie; Wayne Jiang; Fen Li; Shaoying Wu (Pesticide Biochemistry and Physiology, 2026)

A new sesquiterpene lactone and other phytochemicals from the fruits of Magnolia grandiflora and their chemophenetic significance - Qiu-Ye Zhao; Zhen-Quan Li; Shi-Huan Yin; Hui-Ling Zhou; Xin-Ying Wang; Wei-Yang Feng; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Mg2+-driven triple nucleic acid cascades amplify Ru-encoded bimetallic MOF sign PFOA monitoring - Lin-Yi Liu; Ya-Qian Xie; Yue Peng; Si-Yi Ren; Ke-Dao Lai; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2026)

Shenrong Guben Huanshao Pill enhanced stress resistance and extended the lifespan of Caenorhabditis elegans by activating the oxidative stress system via the DAF-16/FOXO signaling pathway - Yi-Nan Yang; Xin Wang; Hong-Fen Jiang; Jie Yang; Subiy Akbara; Xiao-Qin Yang; Hai-Qing Fan; Guo-Lin Chai; Dong-Qing Fei; Fang-Di Hu; Shuang-Xi Qian; Zhan-Xin Zhang (Biogerontology, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

Targeting aryl hydrocarbon receptor signaling attenuates hypertension programmed by maternal Di-2-ethylhexylphthalate exposure - Chien-Ning Hsu; Hsi-Yun Liu; Chih-Yao Hou; Yu-Wei Chen; Guo-Ping Chang-Chien; Shu-Fen Lin; You-Lin Tain (Toxicology and Applied Pharmacology, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

A smart recycling object identification system in vending machines based on edge computing platform and Petri net model - Yi-Nan Lin; Hsiao-Chieh Hsu; Ya-Fen Wu; Victor R.L. Shen (Journal of Environmental Management, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Impact of restoration on reducing carbon emissions from different blue carbon ecosystems - Siqi Nie; Xiaoguang Ouyang; Jia Lin; Fen Guo; Damien T. Maher; Zhaoliang Song; Zhifeng Yang (Ocean & Coastal Management, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

Optimization and kinetic modeling of zinnwaldite grinding process via response surface Methodology (RSM) with flotation experiments - Zhang Lin; Liu Bo; Wei Qian; Jiao Fen (Minerals Engineering, 2026)

Modeling of longwave radiation on coastal building façades based on field measurements - Kaili Yin; Xiaojing Zhang; Jingchao Xie; Haicheng Yang; Jingjie Tan; Fen Lin; Jiaping Liu (Building and Environment, 2026)

Chemical constituents from the fruits of Illicium henryi Diels and their chemotaxonomic significance - Zhen-Xiang Liu; Lin-Fen Ding; Ye-Ting Shi; Zhou Liu; Shi-Huan Yin; Qiu-Ye Zhao; Liu-Dong Song; Xing-De Wu (Biochemical Systematics and Ecology, 2026)

OTUB2 aggravates pathological cardiac hypertrophy through Rac1 activation - Junhui Xing; Lijin Lin; Yi Zhao; Zhen Shen; Yuzhen Wei; Xiaofei Xue; Fen Qin; Hengdao Liu (Human Cell, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

Occurrence, partitioning, and fate of per- and polyfluoroalkyl substances (PFAS) in a full-scale AO–MBR–RO municipal WWTP - Aldeno Rachmad Ika; Shu-Fen Lin; Chih-Lung Wang; Guo-Ping Chang-Chien; Bo-Wun Huang (Journal of Water Process Engineering, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Simultaneous remediation of polycyclic aromatic hydrocarbons (PAHs) contaminated soil using integrated steam-assisted plasma - Kevin Daffa Prasetya; Dwi Rasy Mujiyanti; Jhong-Lin Wu; Sheng-Jie You; Ya-Fen Wang (Environmental Research, 2025)

Interaction between layered mantle flow and progressively thinned lithosphere beneath the Armenia Volcanic Highland: Evidence from seismic azimuthal anisotropy - Jing-Hui Tong; Tai-Lin Tseng; Pei-Ying Patty Lin; Khachatur Meliksetian; Shuo-Fen Chang; Bor-Shouh Huang; Elya Sahakyan; Mikayel Gevorgyan; Lilit Sargsyan (Earth and Planetary Science Letters, 2025)

Single nucleotide variations triggered responsive strip for Helicobacter pylori theranostics - Lin-Min Zhong; Qi-Ling Yang; Xin-Yi Zhong; Xiao-Rong Zhang; Fen-Ying Kong; Shan-Wen Hu; Ai-Lin Liu (Chemical Engineering Journal, 2025)

Three-dimensional molecular engineering of fluorene-based self-assembled monolayers for high-performance inverted perovskite solar cells - Fen Xia; Xiaohan Lin; Jing Zhang; Jun Yin; Jing Li; Xijiao Mu; Song Tu; Binghui Wu; Nanfeng Zheng (Chemical Engineering Journal, 2025)

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

A novel high selectivity, strong acid resistance and antifouling polyamide thin film composite nanofiltration membrane fabricated with 3,3′-diamine-Tröger's base - Liu-Yang Gong; Nian Zhang; Jun-Yan Yu; Yan-Nan Wu; Chen-Jie Wei; He-Lin Zhu; Xue-Li Cao; Li-Fen Liu (Desalination, 2025)

Two pairs of isomeric resin glycosides from Argyreia obtusifolia - Shuo Chen; Yi-Lin Niu; Zhi-Tong Li; Hong-Hua Cui; Yong-Qin Yin; Yan-Fen Chen (Phytochemistry Letters, 2025)

Adaptation and carbon reduction for petroleum contaminated soil remediation in response to climate change-a case study of phytoremediation combined with biochar - Pei-Cheng Cheng; Min-Siou Lin; Chin-Yuan Huang; Shu-Fen Cheng; Yuan-Chung Lin (Journal of Environmental Management, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Dynamic pore engineering in COF-based nanozymes: Construction of hydrogen-bond-mediated confinement catalysis for enhanced asymmetric aldol reactions - Shizhao Wang; Qi Chen; Jiankang Li; Danni Lin; Ka Li; Chuangxin Dong; Xiao Xiao; Fen-Er Chen (Chemical Engineering Journal, 2025)

Dissolved organic matter-mediated metabolic shifts in Chlorella sorokiniana enhanced bioremediation of multi-ionic stress - Ting-Bin Hao; Zhong-Hong Zhang; Lan-Lan Hu; Si-Fen Liu; Jin-Hua Mou; Peizeng Yang; Zhiguo Yuan; Qi Zhang; Srinivasan Balamurugan; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; et al. (Journal of Hazardous Materials, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Metallothioneins protect against isoconazole nitrate-induced antitumor activity through the maintenance of cellular redox homeostasis in hepatocellular carcinoma - Chun-fen Mo; Ya-ruo Lei; Jun Lin; Yi Liu; Zhi-wei Zhao; Wen-jing Xiao; Wen-bai Yan; Wei-wei Zhang (Chemico-Biological Interactions, 2025)

Evaluation and Dissection of Sensory Quality Traits for Potato Taste - Ying Wang; Wan-lin Yang; Fan-kui Zeng; Chun-ni Lei; Qiong-fen Yang; Jian Wang (Potato Research, 2025)
The sensory qualities of potatoes significantly influence consumer preference. This study evaluated the sensory qualities of 66 potato varieties, focusing on representatives of distinct taste types for detailed analysis: sensory evaluation, taste, nutritional components, texture properties, physicochemical characteristics of starch, and volatile aroma compounds. Sensory evaluation of these potato varieties identified the landrace “Kaihua Yangyu” as the most favoured by consumers. The favourable taste of Kai Hua Yang Yu was attributed to (1) soft, dry, and non-sticky texture; (2) starch with higher peak viscosity, easier gelatinisation (below 70 ℃), higher setback value (2776 RVU), and larger granule size (41.63 ± 9.90 μm) compared with other such as YS105 and Cooperation88; and (3) distinctive umami flavour, a trait notably associated with elevated levels of aspartic acid and glutamic acid.

Xanthine oxidase inhibitory constituents from the roots of Ampelopsis japonica - Yu-Lin Li; Fen Liu; Li-Yun Zhao; Han-Xiang Li; Aikebaier Jumai; Zhi-Fang Xu; Sheng-Xiang Qiu (Natural Product Research, 2025)

Response of black tea powder and its fermentation products on growth performance, antioxidant capacity, and gut microbiota of Cherax quadricarinatus - Xian-Jing Zhang; Jiao-Fen Lin; Cheng-Jian Wu; Jie-Quan Xie; You-Shu Cai; Xu-Yin Lin (Frontiers in Marine Science, 2025)
Introduction The overuse of antibiotics in aquaculture has raised concerns, necessitating the exploration of sustainable alternatives. This study evaluated tea-derived additives as potential substitutes. Methods This study evaluated the effects of black tea powder (BTP) and black tea powder-probiotics mixed fermentation product (TPMFP) on Cherax quadricarinatus growth, antioxidant capacity, and gut microbiota. Cherax quadricarinatus were fed diets supplemented with BTP (1–6%) or TPMFP (2%) for 84 days. Results The addition of BTP (<2%) to the feed enhances the weight, carapace length, and muscle protein content of Cherax quadricarinatus , while higher doses (>3%) showed adverse effects. Moreover, the addition of BTP (1%-6%) can significantly reduce the muscle content of CHO, TG, and HDL (P<0.05). The TPMFP group exhibited the highest muscle protein content and significantly elevated hepatopancreatic SOD, GSH-PX, and AKP activities (P < 0.05), indicating improved antioxidant capacity. Gut microbiota analysis revealed dose-dependent shifts, with Proteobacteria dominating (>70%) and Aeromonas increasing with BTP levels. TPMFP significantly increased the α-diversity indices (richness and evenness) of the gut microbiota. The Mantel test confirmed the relationship between the antioxidant function of the microbial community, with Proteobacteria positively correlated with GSH-PX/SOD, while Fusobacteria and Tensionella negatively correlated with antioxidant enzyme activity. Discussion This study provides a foundation for using tea-derived additives as a sustainable alternative to antibiotics in aquaculture.In the future, metagenomic analysis of key metabolic pathways can be combined to optimize the mechanistic explanation of the application and efficacy of BTP and TPMFP.

Two new phenolic derivatives with neuroprotective activities from the fruits of Magnolia denudata - Lin-Fen Ding; Xiang-Yue Zhang; Qiu-Hua Wang; Qiu-Ye Zhao; Shi-Huan Yin; Liu-Dong Song; Xing-De Wu (Phytochemistry Letters, 2025)

Isolation of a new natural bromopyrrole alkaloid agenakasine, a biosynthetically related metabolite laughine, and norzooanemonin from a marine sponge Agelas nakamurai - Chung-Wei Fu; Atallah F. Ahmed; Lin Chiang; Shu-Fen Chiou; Hui-Chun Wang; Jyh-Horng Sheu (Phytochemistry Letters, 2025)

Biomarkers reflecting the toxicity of neonicotinoid insecticides to the central nervous system - Yeru Yang; Xiaoyang Jiao; Fen Yao; Ze Lin; Xiaolin Guo; Meimei Wang; Qingdong Xie; Wenhua Liu; Adela Jing Li; Zhen Wang (Environmental Pollution, 2025)

Thermal-enhanced deep removal of multiple impurities upon pH induction towards selective regeneration of high-purity iron phosphate - Yaohui Xie; Fen Zhang; Shuyu Xiang; Guang Yang; Lin Qu; Fei Han; Liang Xu; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2025)

Four new sesquiterpenoids from Michelia yunnanensis Franch. ex Finet & Gagnep. and their nitric oxide inhibitory activity - Lin-Fen Ding; Yi-Fan Shen; Qiu-Hua Wang; Qiu-Ye Zhao; Shi-Huan Yin; Liu-Dong Song; Xing-De Wu (Phytochemistry Letters, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Konjac glucomannan/xanthan gum film embedding soy protein isolate–tannic acid–iron complexes for blueberry preservation - Zhenzhen Wu; Lin Wang; Chen Ma; Mingming Xu; Xiuqing Guan; Fen Lin; Tengjun Jiang; Xianrui Chen; Nitong Bu; Jie Duan; Wei Liu; Jie Pang (Food Hydrocolloids, 2025)

Predicting and regulating potential zone for heavy metal re-contaminated farmland: Case study in Taiwan - Jieh-Haur Chen; Mu-Chun Su; Meng-Fen Yeh; Wei-Jen Lin; Tzuyang Yu; Ming-Chung Yeh (Environmental Development, 2025)

Associated effects of blood metal(loid) exposure and impaired glucose metabolism in patients with gastric precancerous lesions or gastric cancer - Yuting Zhu; Xiao Lin; Tingting Wang; Sheng Wang; Wuqi Wang; Mengran Ke; Yan Zhu; Bowen Zhang; Princess Ofosuhemaa; Yalei Wang; Mingjun Hu; Wanshui Yang; et al. (BioMetals, 2025)

Discovery of phenoxazine congeners as novel α-glucosidase inhibitors and identification of their biosynthetic gene cluster from Streptomyces sp. CB00316 - Lin Jiang; Pingzhi Huang; Aijie Li; Bin Fen; Yani Zhong; Caijun Tang; Guangling Wu; Wenlei Wang; Yuhan Chen; Jian Pan; Genyun Tang; Hong Pu (Archives of Microbiology, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Investigating Catching Hotspots of Fishing Boats: A Framework Using BeiDou Big Data and Deep Learning Algorithms - Fen Wang; Xingyu Liu; Tanxue Chen; Hongxiang Feng; Qin Lin (Journal of Marine Science and Engineering, 2025)
Illegal, unreported, and unregulated (IUU) fishing significantly threatens marine ecosystems, disrupts the ecological balance of the oceans, and poses serious challenges to global fisheries management. This contribution presents the efficacy of China’s summer fishing moratorium using BeiDou vessel monitoring system (VMS) data from 2805 fishing vessels in the East China Sea and Yellow Sea, integrated with a deep learning framework for spatiotemporal analysis. A preprocessing protocol addressing multidimensional noise in raw VMS datasets was developed, incorporating velocity normalization and gap filling to ensure data reliability. The CNN-BiLSTM hybrid model emerged as optimal for fishing behavior classification, achieving 89.98% accuracy and an 87.72% F1 score through synergistic spatiotemporal feature extraction. Spatial analysis revealed significant policy-driven reductions in fishing intensity during the moratorium (May–August), with hotspot areas suppressed to sporadic coastal distributions. However, concentrated vessel activity in Zhejiang’s nearshore waters suggested potential illegal fishing. Post-moratorium, fishing hotspots expanded explosively, peaking in October and clustering in Yushan, Zhoushan, and Yangtze River estuary fishing grounds. Quarterly patterns identified autumn–winter 2021 as peak fishing seasons, with hotspots covering >80% of East China Sea grounds. The framework enables real-time fishing state detection and adaptive spatial management via dynamic closure policies. The findings underscore the need for strengthened surveillance during moratoriums and post-ban catch regulation to mitigate overfishing risks.

Origin and metamorphism of ophiolitic serpentinites from the Yuli belt, eastern Taiwan: new findings and tectonic implications - Dominikus Deka Dewangga; Chin-Ho Tsai; Yoshiyuki Iizuka; Ilona Talvikki Sakaguchi; Yui Kouketsu; Sun-Lin Chung; Chi-Yu Lee; Wen-Yen Chang; Huei-Fen Chen (International Geology Review, 2025)

Examining the determinants of blockchain technology-enabled maritime supply chain system adoption intention: Does market turbulence play a moderating role? - Hsiu-Fen Lin (Marine Policy, 2025)

Application and electrochemical depression mechanism of sodium sulfite on the flotation separation of galena–pyrite mixed concentrate in Yiliang typical high‑sulfur lead–zinc deposit - Zhicheng Liu; Fen Jiao; Yanfang Cui; Xiang Lin; Wenqing Qin; Qian Wei (Geochemistry, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Ocean as source or sink for legacy persistent organic pollutants - Chuchu Chen; Fen Yang; Qiang Wu; Jun Yu; Jingqian Xie; Yin Fang; Tian Lin (Journal of Hazardous Materials, 2025)

Enrichment behavior of lithium enhanced by multistage water leaching of overhaul slag roasted clinker - Liangmin Dong; Fen Jiao; Wei Liu; Lin Zhang (Journal of Environmental Chemical Engineering, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

The Proteomic Analysis of Chronic Migraine Exosomes Reveals Disease Patterns and Potential Biomarkers - Weiyun Zhang; Fen Wan; Lihui Duan; Wen Tao; Jun Wang; Lin Huang; Lanyun Yan (Molecular Neurobiology, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Global occurrence, food web transfer, and human health risks of polycyclic aromatic hydrocarbons in biota - Jingqian Xie; Ruo Lan; Li Zhang; Jun Yu; Xinran Liu; Zhiyang You; Fen Yang; Tian Lin (Science of The Total Environment, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Spatiotemporal evolution of land use efficiency in 357 cities across mainland China from 2000 to 2020 based on SDG 11.3.1 - Min Huang; Fen Liu; Daohong Gong; Hui Lin; Yong Chen; Bisong Hu; Yong Ge; Changjiang Xiao (Science of The Total Environment, 2024)

Community prevention and standardized clinical treatment jointly improve cancer outcome: Real-world evidence from an esophageal cancer patient cohort study - Ji Ke; Fangfang Liu; Wei Yang; Ruiping Xu; Lei Chen; Wenlei Yang; Yu He; Zhen Liu; Bolin Hou; Liqun Zhang; Miaoping Lin; Lixin Zhang; et al. (Science Bulletin, 2024)

Aluminate-activated nano-SiO2 for enhancing water vapor barrier properties in polymers films: A safe and effective strategy - Chuang-Chuang Zhao; Qin-Bao Lin; Yan-Fen Chen; Huai-Ning Zhong; David Julian McClements; Da Ma (Food Packaging and Shelf Life, 2024)

Enhanced therapeutic potential of Flotillins-modified MenSCs by improve the survival, proliferation and migration - Fangfang Cheng; Longkai Ji; Pan Li; Zhisheng Han; Yanan He; Fen Yang; Zhihao Xu; Yonghai Li; Tao Ruan; Xinxing Zhu; Juntang Lin (Molecular Biology Reports, 2024)

Retraction Note to: LPS Pretreatment Provides Neuroprotective Roles in Rats with Subarachnoid Hemorrhage by Downregulating MMP9 and Caspase3 Associated with TLR4 Signaling Activation - Ting-Hua Wang; Liu-Lin Xiong; Shuai-Fen Yang; Chao You; Qing-Jie Xia; Yang Xu; Piao Zhang; Shu-Fen Wang; Jia Liu (Molecular Neurobiology, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Rutin alleviates Pb-induced oxidative stress, inflammation and cell death via activating Nrf2/ARE system in SH-SY5Y cells - Fen Li; Lin Zhang; Xingxu Zhang; Qimeng Fang; Yingshun Xu; Hui Wang (NeuroToxicology, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Self-conductive organic quaternary ammonium lithium salt-based ultra-concentrated electrolyte for safe lithium metal batteries - Yijing Liu; Sibo Qiao; Jinrui Hu; Fen Guo; Lixia Bao; Weichao Lin; Xiao Xu; Pengpeng Liu; Weibo Kong; Yuehan Jia; Jiliang Wang (Chemical Engineering Journal, 2024)

Improvement of the Diagnostic Method for the Detection of Parasite Eggs Using the Formalin Ethyl Acetate Concentration Technique - Jia-Hung Liou; Te-Ling Lu; Hui-Fen Cheng; Long-Wei Lin; Po-Cheng Kung; Hong-Jing Chuang; Te-Hsiu Lee; Chee-Hong Chan; Te-Jung Lu (Acta Parasitologica, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

Baicalin attenuates acute skin damage induced by ultraviolet B via inhibiting pyroptosis - Zuohao Liu; Bingrong Dang; Zhen Li; Xingsheng Wang; Yuhan Liu; Fen Wu; Xinhui Cao; Chunming Wang; Changjun Lin (Journal of Photochemistry and Photobiology B: Biology, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Gelselegine-gelsedine type bisindoles as well as the units from Gelsemium elegans with promoting proliferation of oral mucosa fibroblast cells - Jing Lin; Jing Wu; Mei-Fen Bao; Sumet Kongkiatpaiboon; Xiang-Hai Cai (Phytochemistry, 2024)

LCQDs modified Bi2MoO6 hydrangea composite photocatalyst for tetracycline degradation from wastewater: Performance, efficiency, and adsorption synergistic photocatalytic mechanism - Dan Xu; Hong Yan; Fen Li; Yuchen Lin; Yuanbo Zhang; Cailian Yu (Journal of Environmental Chemical Engineering, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Controllable lignin valorization to value-added aromatic chemicals by a UV-assisted ternary heterogeneous photo-fenton catalytic system - Fen Wang; Lin Zhang; Zhiping Wu; Wenbo Peng; Peng Zhan; Lishu Shao; Hui Wang; Yan Qing; Hanxue Lin; Quan Wei; Na Liu; Zhaohui Tong (Fuel, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Microcystin-LR and polystyrene microplastics jointly lead to hepatic histopathological damage and antioxidant dysfunction in male zebrafish - Wang Lin; Fen Hu; Fang Liu; Ling Liao; Ling Ling; Li Li; Jifeng Yang; Pinhong Yang (Environmental Pollution, 2024)

The interleukin enhancer binding factor-2 (ILF2) gene in Penaeus japonicus shrimp: cloning, tissue distribution, and antiviral effects - Junying Xu; Fen Li; Junfeng Zhang; Lin Wang; Xinbo Liu; Wenyu Xue; Yinghua Shi; Yalei Cui (Aquaculture International, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Selective flotation separation of smithsonite from calcite by using cupferron - Zhengquan Zhang; Lin Zhang; Fen Jiao; Congren Yang; Qian Wei; Wenqing Qin; Chen Wang; Xiang Lin (Minerals Engineering, 2024)

Sustainable paramylon production from food waste by Euglena gracilis using a waste-based cell immobilisation technique - Jin-Hua Mou; Si-Fen Liu; Li-Li Yang; Zi-Hao Qin; Yu-Feng Yang; Zhen-Yao Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2024)

Occurrence and bioaccumulation of parabens and their metabolites in the biota from a subtropical freshwater river ecosystem: Implications for human exposure - Yiling Lin; Yanan Zhao; Yuxian Liu; Yongyin Lan; Jiamin Zhu; Yanpeng Cai; Fen Guo; Feilong Li; Yuan Zhang; Zhihao Xu; Jingchuan Xue (Environmental Research, 2024)

The brominated flame retardant tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl ether) as well as hexabromocyclododecane lead to lipid disorders in mice - Xuan-Yue Chen; Yuan-Yuan Li; Lin Lv; Yi-Ming Xiong; Zhan-Fen Qin (Environmental Pollution, 2024)

Crocin alleviates neurotoxicity induced by bupivacaine in SH-SY5Y cells with inhibition of PI3K/AKT signaling - Lili Lin; Zhen Chen; Jun Li; Jianye Peng; Jian Wang; Mingjun Feng; Tiancheng Liu; Mengli Zhang; Xian Wu; Fen Ai; Caijie Shen (Genes & Genomics, 2024)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Non-targeted analysis and risk assessment of intentionally and non-intentionally added substances migrating from the emerging biodegradable food contact material poly(butylene adipate-co-terephthalate)/modified starch blend film - Jun Lin; Wei-Liang Wu; Ai-Hua Zhong; Yan-Ping Xian; Huai-Ning Zhong; Ben Dong; Ming Liang; Jun-Peng Hu; Yong-Ning Wu; Xing-Fen Yang; Hai-Xia Sui; Quan Zhou (Food Packaging and Shelf Life, 2023)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

Inhibitory mechanism of carboxymethyl chitosan-lotus seedpod oligomeric procyanidin nanoparticles on dietary advanced glycation end products released from glycated casein during digestion - Qian Wu; Fen Zhang; Yaxiong Wang; Jia Yan; Chen Zhou; Yang Xu; Jianhua Xu; Lin Shi; He Xiong; Nianjie Feng (Food Research International, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Identification of circRNAs and circRNA-mRNA network of Epinephelus coioides during Singapore grouper iridovirus infection - Yi-Jie Cai; Wei Huang; Liang-Yuan Zhu; Yun-Xiang Lin; Cui-Fen Huang; Wen-Feng Yang; Jia-Lin Zhou; Jun-De Dong; Wei-Hua Zhou; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Navigating practical applications of food waste valorisation based on the effects of food waste origins and storage conditions - Jin-Hua Mou; Zi-Hao Qin; Yu-Feng Yang; Si-Fen Liu; Wei Yan; Lan Zheng; Ya-Hui Miao; Hong-Ye Li; Patrick Fickers; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Identification and protective role of CD34+ stromal cells/telocytes in experimental autoimmune encephalomyelitis (EAE) mouse spleen - Ganesh Dama; Xiaoxi Hu; Yushan Yan; Yonghai Li; Han Li; Fen Yang; Yanli Liu; Juntang Lin (Histochemistry and Cell Biology, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Activated AMPK-mediated glucose uptake and mitochondrial dysfunction is critically involved in the glutamate-induced oxidative injury in HT22 cell - Shao-Peng Lin; Jingyi Bu; Shan Ye; Qiangda Xie; Jue-Xian Wei; Xiaofang Yin; Fen Mei; Pei-Yi Lin; Xiao-Hui Chen (Tissue and Cell, 2023)

Extreme cooling of 12.5 °C triggered by Typhoon Fungwong (2008) - Zhe-Wen Zheng; Jia-Yi Lin; Ganesh Gopalakrishnan; Yi-Rui Chen; Doon-Jing Doong; Chung-Ru Ho; Quanan Zheng; Chau-Ron Wu; Chen-Fen Huang (Ocean Modelling, 2023)

A case of A133V genetic Creutzfeldt–Jakob disease presenting with bilateral thalamic lesions and atypical clinical features - Shi-Lin Yang; Shu-Fen Chen; Chong-Bo Zhao; Xiang Han (Acta Neurologica Belgica, 2023)

Non-targeted screening for contaminants derived from food contact water-borne coatings and risk assessment based on (Q)SAR matrix - Qing-Hua Yang; Qin-Bao Lin; Jia Liao; Hong-Sheng Ma; Xiao-Fen Wei; Yue Wang; Xiaowen Xu (Food Packaging and Shelf Life, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Dual bio-degradative pathways of di-2-ethylhexyl phthalate by a novel bacterium Burkholderia sp. SP4 - Yen-Shun Hsu; Yung-Hsin Liu; Chu-Hsuan Lin; Chih-Hsuan Tsai; Whei-Fen Wu (World Journal of Microbiology and Biotechnology, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Study on the chemical composition of Caesalpinia sinensis - Lu-Fen Leng; Qi Lai; Dian Lv; Jun-Lin Yin; Guang-Zhi Zeng (Natural Product Research, 2022)

Live on the land and fed by the sea: diverse subsistence economies in the Neolithic Dawenkou Period in Shandong Peninsula, China - Minghao Lin; Yanbo Song; Fen Wang; Zebing Wang; Songtao Chen (Archaeological and Anthropological Sciences, 2022)

Genetic Diversity Evaluation and Population Structure Analysis of Red Swamp Crayfish (Procambarus clarkii) from Lakes and Rice Fields by SSR Markers - Xin-Fen Guo; Min Liu; Yu-Lin Zhou; Wen-Yu Wei; Zhi Li; Li Zhou; Zhong-Wei Wang; Jian-Fang Gui (Fishes, 2022)
The red swamp crayfish (Procambarus clarkii) is an important aquatic animal and has developed as a popular aquaculture species in China. In this study, a total of 72,839 SSR motifs were identified from transcriptional data, and 20 microsatellite markers of them were finally developed to assess the genetic diversities of seven wild populations from natural lakes and nine cultured populations from rice fields. Genetic diversity was slightly higher in the cultured populations than in the wild populations. The degree of genetic differentiation between cultured populations is slight, while a moderate to a large degree of genetic differentiation between wild populations and most of the variations occurred within individuals (79%). The analysis of cluster, principal coordinate analysis and STRUCTURE were similar, and they showed that isolation-by-distance pattern was not significant. The microsatellite markers developed in this study can not only be used for genetic monitoring of population but also provide important information for the management of breeding and cultured population in red swamp crayfish.

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Electrical Impedance Tomography Analysis Between Two Similar Respiratory System Compliance During Decremetal PEEP Titration in ARDS Patients - Po-Lan Su; Wei-Chieh Lin; Yen-Fen Ko; Kuo-Sung Cheng; Chang-Wen Chen (Journal of Medical and Biological Engineering, 2021)
Purpose The positive end-expiratory pressure (PEEP) level with best respiratory system compliance (Crs) is frequently used for PEEP selection in acute respiratory distress syndrome (ARDS) patients. On occasion, two similar best Crs (where the difference between the Crs of two PEEP levels is < 1 ml/cm H 2 O) may be identified during decremental PEEP titration. Selecting PEEP under such conditions is challenging. The aim of this study was to provide supplementary rationale for PEEP selection by assessing the global and regional ventilation distributions between two PEEP levels in this situation. Methods Eight ARDS cases with similar best Crs at two different PEEP levels were analyzed using examination-specific electrical impedance tomography (EIT) measures and airway stress index (SIaw). Five Crs were measured at PEEP values of 25 cm H 2 O (PEEP 25 ), 20 cm H 2 O (PEEP 20 ), 15 cm H 2 O (PEEP H ), 11 cm H 2 O (PEEP I ), and 7 cm H 2 O (PEEP L ). The higher PEEP value of the two PEEPs with similar best Crs was designated as PEEP upper , while the lower designated as PEEP lower . Results PEEP H and PEEP I shared the best Crs in two cases, while similar Crs was found at PEEP I and PEEP L in the remaining six cases. SIaw was higher with PEEP upper as compared to PEEP lower (1.06 ± 0.10 versus 0.99 ± 0.09, p = 0.05). Proportion of lung hyperdistension was significantly higher with PEEP upper than PEEP lower (7.0 ± 5.1% versus 0.3 ± 0.5%, p = 0.0002). In contrast, proportion of recruitable lung collapse was higher with PEEP lower than PEEP upper (18.6 ± 4.4% versus 5.9 ± 3.7%, p < 0.0001). Cyclic alveolar collapse and reopening during tidal breathing was higher at PEEP lower than PEEP upper (34.4 ± 19.3% versus 16.0 ± 9.1%, p = 0.046). The intratidal gas distribution (ITV) index was also significantly higher at PEEP lower than PEEP upper (2.6 ± 1.3 versus 1.8 ± 0.7, p = 0.042). Conclusions PEEP upper is a rational selection in ARDS cases with two similar best Crs. EIT provides additional information for the selection of PEEP in such circumstances.

Modeling aerosol transmission of SARS-CoV-2 from human-exhaled particles in a hospital ward - Lip Huat Saw; Bey Fen Leo; Norefrina Shafinaz Md Nor; Chee Wai Yip; Nazlina Ibrahim; Haris Hafizal Abd Hamid; Mohd Talib Latif; Chin Yik Lin; Mohd Shahrul Mohd Nadzir (Environmental Science and Pollution Research, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Application of the modified cytosine base-editing in the cultured cells of bama minipig - Jia-sheng Pan; Zi-sheng Lin; Jian-cong Wen; Jian-feng Guo; Xia-hui Wu; Ying-ying Liu; Wen-jun Lai; Qi-ying Liang; Yong-shi Xie; Yi-rou Chen; Yi-hong Chen; Ai-fen Yan; et al. (Biotechnology Letters, 2021)

Legal Issues for Artificial Floating Islands - Maarten M. B. Flikkema; Fen-Yu (Vicky) Lin; Pernille P. J. van der Plank; Jos Koning; Olaf Waals (Frontiers in Marine Science, 2021)
Developments of multi-use floating islands are accelerated by an increase in offshore activities and pressing needs to create extra space in coastal regions for the surging population. The Horizon 2020 EU funded research project Space@Sea developed a modular floating island concept for offshore multi-use applications and examined current legal issues and barriers concerning its development. In this paper a floating island is defined to be “an artificially created floater, or set of connected floaters, moored to the seabed of which the topside can be used for activities similar to activities on land”. This paper aims to delve into governance issues like the assignment of authority on a multi-use floating island and the shift from regulating offshore living for working purposes to living purposes, as well as maritime law and property law (using the Netherlands as case study). Within the Exclusive Economic Zone (EEZ) a coastal state can establish, locate, and govern the floating island. For the high seas the International Maritime Organization (IMO) is the most probable organization to initiate a discussion on settlement of floating islands. For each activity on the floating island, limiting criteria regarding motions as well as safety rules and regulations need to be established. Industry and housing will have completely different requirements regarding safety which will not be possible to fit in a one size fits all regulation. This case study shows that current Dutch property law prohibit the division of ownership of buildings built on floating objects. They can only be owned together as one object. For urban expansion, future inhabitants will want to have the possibility to buy property, requiring an amendment of current property law. It is to be expected that other countries will have similar or additional governance challenges. The Space@Sea project has developed a technical solution for floating islands which have identified barriers for multi-use in the rules and regulations described in this paper. The paper urges the responsible institutions and stakeholders to take on their roles in overcoming these barriers.

Performance Comparison of the Deep Learning and the Human Endoscopist for Bleeding Peptic Ulcer Disease - Hsu-Heng Yen; Ping-Yu Wu; Pei-Yuan Su; Chia-Wei Yang; Yang-Yuan Chen; Mei-Fen Chen; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2021)
Purpose Management of peptic ulcer bleeding is clinically challenging. Accurate characterization of the bleeding during endoscopy is key for endoscopic therapy. This study aimed to assess whether a deep learning model can aid in the classification of bleeding peptic ulcer disease. Methods Endoscopic still images of patients ( n = 1694) with peptic ulcer bleeding for the last 5 years were retrieved and reviewed. Overall, 2289 images were collected for deep learning model training, and 449 images were validated for the performance test. Two expert endoscopists classified the images into different classes based on their appearance. Four deep learning models, including Mobile Net V2, VGG16, Inception V4, and ResNet50, were proposed and pre-trained by ImageNet with the established convolutional neural network algorithm. A comparison of the endoscopists and trained deep learning model was performed to evaluate the model’s performance on a dataset of 449 testing images. Results The results first presented the performance comparisons of four deep learning models. The Mobile Net V2 presented the optimal performance of the proposal models. The Mobile Net V2 was chosen for further comparing the performance with the diagnostic results obtained by one senior and one novice endoscopists. The sensitivity and specificity were acceptable for the prediction of “normal” lesions in both 3-class and 4-class classifications. For the 3-class category, the sensitivity and specificity were 94.83% and 92.36%, respectively. For the 4-class category, the sensitivity and specificity were 95.40% and 92.70%, respectively. The interobserver agreement of the testing dataset of the model was moderate to substantial with the senior endoscopist. The accuracy of the determination of endoscopic therapy required and high-risk endoscopic therapy of the deep learning model was higher than that of the novice endoscopist. Conclusions In this study, the deep learning model performed better than inexperienced endoscopists. Further improvement of the model may aid in clinical decision-making during clinical practice, especially for trainee endoscopist.

Exploring the environmental and economic potential for biogas production from swine manure wastewater by life cycle assessment - Meng-Fen Shih; Chyi-How Lay; Chiu-Yue Lin; Shen-Ho Chang (Clean Technologies and Environmental Policy, 2021)

Correction to: Delineation of potential hot spots of aeolian dust using normalized difference water index - Chao-Yuan Lin; Shu-Fen Tsai; Chih-Yun Wang; Cheng-Yu Lin (Theoretical and Applied Climatology, 2021)

Delineation of potential hot spots of aeolian dust using normalized difference water index - Chao-Yuan Lin; Shu-Fen Tsai; Chih-Yun Wang; Cheng-Yu Lin (Theoretical and Applied Climatology, 2021)

Collapsin response mediator protein 5 (CRMP5) modulates susceptibility to chronic social defeat stress in mice - Yu-Fen Lin; Kao Chin Chen; Yen Kuang Yang; Ya-Hsin Hsiao (Molecular Neurobiology, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Brain voxel-based morphometry correlates of emotion dysregulation in attention-deficit hyperactivity disorder - Chia-Jui Tsai; Hsiang-Yuan Lin; Isaac Wen-Yih Tseng; Susan Shur-Fen Gau (Brain Imaging and Behavior, 2021)

Wetland Ecosystem Service Dynamics in the Yellow River Estuary under Natural and Anthropogenic Stress in the Past 35 Years - Huijuan Xia; Lusan Liu; Junhong Bai; Weijing Kong; Kuixuan Lin; Fen Guo (Wetlands, 2020)

Boys with autism spectrum disorder have distinct cortical folding patterns underpinning impaired self-regulation: a surface-based morphometry study - Hsing-Chang Ni; Hsiang-Yuan Lin; Yu-Chieh Chen; Wen-Yih Isaac Tseng; Susan Shur-Fen Gau (Brain Imaging and Behavior, 2020)

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

Impact of Maternal Separation on Dopamine System and its Association with Parkinson's Disease - Kai-jie He; Yu-ting Zhang; Shi-zhuang Wei; Shu-min Jiang; Lin Xu; Chao Ren; Fen Wang (NeuroMolecular Medicine, 2020)

Automatic Striatal ROI Delineation for Semi-quantitative Analysis of 99mTc-TRODAT-1 Brain SPECT Imaging - Bang-Hung Yang; Kang-Ping Lin; Mei-Fen Chen; Jui-Hung Weng; Pan-Fu Kao; Wen-Chen Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2020)

The maize B chromosome is capable of expressing microRNAs and altering the expression of microRNAs derived from A chromosomes - Yen-Hua Huang; Shu-Fen Peng; Yao-Pin Lin; Ya-Ming Cheng (Chromosome Research, 2020)

Novel B-chromosome-specific transcriptionally active sequences are present throughout the maize B chromosome - Zi-Jie Hong; Jun-Xiang Xiao; Shu-Fen Peng; Yao-Pin Lin; Ya-Ming Cheng (Molecular Genetics and Genomics, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

TLR-2-mediated metabolic reprogramming participates in polyene phosphatidylcholine-mediated inhibition of M1 macrophage polarization - Ting-Ting Feng; Xiao-Ying Yang; Shan-Shan Hao; Fen-Fen Sun; Ye Huang; Qi-Si Lin; Wei Pan (Immunologic Research, 2020)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Evaluation of Coherence Between ECG and PPG Derived Parameters on Heart Rate Variability and Respiration in Healthy Volunteers With/Without Controlled Breathing - Hao-Yu Jan; Mei-Fen Chen; Tieh-Cheng Fu; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2019)

Characterization of the complete chloroplast genome of Euryodendron excelsum (Pentaphylacaceae), a critically endangered species endemic to China - Xiang-gang Shi; Wei-xi Li; Fen Xing; Yu-bin Zhou; Wu-xia Guo; Ye-lin Huang (Conservation Genetics Resources, 2019)

The analysis of clinical and laboratory data: a large outbreak of dengue fever in Chaozhou, Guangdong province, China - Fen Lin; Hui Yang; Lin Zhang; Sen-Hai Fang; Xiao-Fen Zhan; Li-Ye Yang (Archives of Virology, 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

The Mycobacterial Adjuvant Analogue TDB Attenuates Neuroinflammation via Mincle-Independent PLC-γ1/PKC/ERK Signaling and Microglial Polarization - Mahendravarman Mohanraj; Ponarulselvam Sekar; Horng-Huei Liou; Shwu-Fen Chang; Wan-Wan Lin (Molecular Neurobiology, 2019)

Contrastive removal of oxytetracycline and chlortetracycline from aqueous solution on Al-MOF/GO granules - Lin-ling Yu; Zi-fen Luo; Ying-ying Zhang; Shi-chuan Wu; Cao Yang; Jian-hua Cheng (Environmental Science and Pollution Research, 2019)

Role of cytoplasmic lncRNAs in regulating cancer signaling pathways - Pei-fen Fu; Xin Zheng; Xiao Fan; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Microtremor survey and stability analysis of a soil-rock mixture landslide: a case study in Baidian town, China - Wen-wei Gao; Wei Gao; Rui-lin Hu; Pei-fen Xu; Jia-guo Xia (Landslides, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Characterization of some selected mud volcanoes of southern Taiwan - Arvind Kumar; Tsung-Han Yang; Vivek Walia; Yi-Chun Sung; Hasio-Fen Lee; Shih-Jung Lin; Kuo-Liang Wen (Acta Geophysica, 2018)

Identification of a new type tadalafil analogue in a supplement product - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2018)

Umbilical Cord Mesenchymal Stem Cells Conditioned Medium Promotes Aβ25-35 phagocytosis by Modulating Autophagy and Aβ-Degrading Enzymes in BV2 Cells - Zhihao Xu; Wenbin Nan; Xiaoyue Zhang; Yuliang Sun; Jichao Yang; Kecheng Lu; Yalin Liu; Yaoxin Gao; Fen Yang; Wenchao Mao; Xuekun Xing; Jiang Du; et al. (Journal of Molecular Neuroscience, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Fast trace determination of nine odorant and estrogenic chloro- and bromo-phenolic compounds in real water samples through automated solid-phase extraction coupled with liquid chromatography tandem mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-xian Lian; Chuang-tao Yang; Qing Lin; Hua Yin; Zhang Lin; Zhi Dang (Environmental Science and Pollution Research, 2018)

Metaproteomics of marine viral concentrates reveals key viral populations and abundant periplasmic proteins in the oligotrophic deep chlorophyll maximum of the South China Sea - Zhang‐Xian Xie; Feng Chen; Shu‐Feng Zhang; Ming‐Hua Wang; Hao Zhang; Ling‐Fen Kong; Min‐Han Dai; Hua‐Sheng Hong; Lin Lin; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Viral concentrates (VCs), containing bioinformative DNA and proteins, have been used to study viral diversity, viral metagenomics and virus–host interactions in natural ecosystems. Besides viruses, VCs also contain many noncellular biological components including diverse functional proteins. Here, we used a shotgun proteomic approach to characterize the proteins of VCs collected from the oligotrophic deep chlorophyll maximum (DCM) of the South China Sea. Proteins of viruses infecting picophytoplankton, that is, cyanobacteria and prasinophytes, and heterotrophic bacterioplankton, such as SAR11 and SAR116, dominated the viral proteome. Almost no proteins from RNA viruses or known gene transfer agents were detected, suggesting that they were not abundant at the sampling site. Remarkably, nonviral proteins made up about two thirds of VC proteins, including overwhelmingly abundant periplasmic transporters for nutrient acquisition and proteins for diverse cellular processes, that is, translation, energy metabolism and one carbon metabolism. Interestingly, three 56 kDa selenium‐binding proteins putatively involved in peroxide reduction from gammaproteobacteria were abundant in the VCs, suggesting active removal of peroxide compounds at DCM. Our study demonstrated that metaproteomics provides a valuable avenue to explore the diversity and structure of the viral community and also the pivotal biological functions affiliated with microbes in the natural environment.

Erratum to: LPS Pretreatment Provides Neuroprotective Roles in Rats with Subarachnoid Hemorrhage by Downregulating MMP9 and Caspase3 Associated with TLR4 Signaling Activation - Ting-Hua Wang; Liu-Lin Xiong; Shuai-Fen Yang; Chao You; Qing-Jie Xia; Yang Xu; Piao Zhang; Shu-Fen Wang; Jia Liu (Molecular Neurobiology, 2017)

RETRACTED ARTICLE: LPS Pretreatment Provides Neuroprotective Roles in Rats with Subarachnoid Hemorrhage by Downregulating MMP9 and Caspase3 Associated with TLR4 Signaling Activation - Ting-Hua Wang; Liu-Lin Xiong; Shuai-Fen Yang; Chao You; Qing-Jie Xia; Yang Xu; Piao Zhang; Shu-Fen Wang; Jia Liu (Molecular Neurobiology, 2017)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Two new geranylphenylacetate glycosides from the barks of Cinnamomum cassia - Jun-Fen Zeng; Hu-Cheng Zhu; Jian-Wu Lu; Lin-Zhen Hu; Jin-Chun Song; Yong-Hui Zhang (Natural Product Research, 2017)

Modern greenhouse culture of juvenile soft-shelled turtle, Pelodiscus sinensis - Jing Zhang; Fen Wang; Ye-Lin Jiang; Guan-Jun Hou; Yun-Sheng Cheng; Hong-Lian Chen; Xiang Li (Aquaculture International, 2017)

Isolation and identification of a novel sildenafil analogue adulterant in herbal products - Ya-Tze Lin; Yen-Chun Huang; Hui-Chun Lee; Chen-Hsiang Liao; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2017)

A Review of the Functional and Anatomical Default Mode Network in Schizophrenia - Mao-Lin Hu; Xiao-Fen Zong; J. John Mann; Jun-Jie Zheng; Yan-Hui Liao; Zong-Chang Li; Ying He; Xiao-Gang Chen; Jin-Song Tang (Neuroscience Bulletin, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Effects of soybean isoflavone on intestinal antioxidant capacity and cytokines in young piglets fed oxidized fish oil - Lin Huang; Xian-yong Ma; Zong-yong Jiang; You-jun Hu; Chun-tian Zheng; Xue-fen Yang; Li Wang; Kai-guo Gao (Journal of Zhejiang University-SCIENCE B, 2016)

Identification of a new sildenafil analogue adulterant, desethylcarbodenafil, in a herbal supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Ya-Tze Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

Minocycline ameliorates d-galactose-induced memory deficits and loss of Arc/Arg3.1 expression - Xu Li; Fen Lu; Wei Li; Jun Xu; Xiao-Jing Sun; Ling-Zhi Qin; Qian-Lin Zhang; Yong Yao; Qing-Kai Yu; Xin-Liang Liang (Molecular Biology Reports, 2016)

Simultaneous determination of estrogenic odorant alkylphenols, chlorophenols, and their derivatives in water using online headspace solid phase microextraction coupled with gas chromatography-mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-Xian Lian; Chuangtao Yang; Qing Lin; Hua Yin; Zhi Dang (Environmental Science and Pollution Research, 2016)

Identification of a new tadalafil analogue, dipropylaminopretadalafil, in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

Scutellarin Alleviates Behavioral Deficits in a Mouse Model of Multiple Sclerosis, Possibly Through Protecting Neural Stem Cells - Wei-Wei Wang; Lin Lu; Tian-Hao Bao; Hong-Miao Zhang; Jing Yuan; Wei Miao; Shu-Fen Wang; Zhi-Cheng Xiao (Journal of Molecular Neuroscience, 2016)

New phenyl derivatives from endophytic fungus Botryosphaeria sp. SCSIO KcF6 derived of mangrove plant Kandelia candel - Zhi-ran Ju; Xiaochu Qin; Xiu-ping Lin; Jun-feng Wang; Kumaravel Kaliyaperumal; Yong-qi Tian; Juan Liu; Fen Liu; Zhengchao Tu; Shi-hai Xu; Yonghong Liu (Natural Product Research, 2016)

Separation and identification of a novel tadalafil analogue adulterant in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Ying Li; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2015)

Endoplasmic Reticulum Stress: Relevance and Therapeutics in Central Nervous System Diseases - Hong-Yu Zhang; Zhou-guang Wang; Xiang-Hong Lu; Xiao-Xia Kong; Fen-Zan Wu; Li Lin; Xiaohua Tan; Li-Bing Ye; Jian Xiao (Molecular Neurobiology, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Characterization of four B-chromosome-specific RAPDs and the development of SCAR markers on the maize B-chromosome - Kuo-Wei Kao; Chien-Yu Lin; Shu-Fen Peng; Ya-Ming Cheng (Molecular Genetics and Genomics, 2015)

Production of Arachidonic and Eicosapentaenoic Acids by the Marine Oomycete Halophytophthora - Ka-Lai Pang; Han-Jia Lin; Hung-Yun Lin; Yu-Fen Huang; Yi-Min Chen (Marine Biotechnology, 2015)

Exploring the benefits of growing bioenergy crops to activate lead-contaminated agricultural land: a case study on sweet potatoes - Shu-Fen Cheng; Chin-Yuan Huang; Kuo-Lin Chen; Sheng-Chien Lin; Yung-Cheng Lin (Environmental Monitoring and Assessment, 2015)

Modulation of p75 neurotrophin receptor under hypoxic conditions induces migration and invasion of C6 glioma cells - Ting-Chung Wang; Sheng-jie Luo; Chun-Liang Lin; Pey-Jium Chang; Miao-Fen Chen (Clinical & Experimental Metastasis, 2015)

Cathepsin B is involved in the heat shock induced cardiomyocytes apoptosis as well as the anti-apoptosis effect of HSP-70 - Shu-Fen Hsu; Chuan-Chih Hsu; Bor-Chih Cheng; Cheng-Hsien Lin (Apoptosis, 2014)

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

New species and new records of Rhytismataceae from Japan - Zhi-Jie Li; Ning Cao; Hui-Fen Chen; J. E. Taylor; Cheng-Lin Hou (Mycological Progress, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Relating vegetation dynamics to temperature and precipitation at monthly and annual timescales in Taiwan using MODIS vegetation indices - Chung-Te Chang; Su-Fen Wang; Matthew A. Vadeboncoeur; Teng-Chiu Lin (International Journal of Remote Sensing, 2014)

Effect of air-drying and oven-drying treatment on Cr(VI) content and Cr bond forms in soil - Shu-Fen Cheng; Chi-Ying Lai; Sheng-Jie Lin; Chin-Yuan Huang (Environmental Monitoring and Assessment, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

The role of MrbHLH1 and MrMYB1 in regulating anthocyanin biosynthetic genes in tobacco and Chinese bayberry (Myrica rubra) during anthocyanin biosynthesis - Xiao-Fen Liu; Xue-Ren Yin; Andrew C. Allan; Kui Lin-Wang; Yan-Na Shi; Yu-Ji Huang; Ian B. Ferguson; Chang-Jie Xu; Kun-Song Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

Effect of Scour on the Behavior of Laterally Loaded Single Piles in Marine Clay - Fen Li; Jie Han; Cheng Lin (Marine Georesources & Geotechnology, 2013)

Erratum to: Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2013)

Peanut as a potential crop for bioenergy production via Cd-phytoextraction: A life-cycle pot experiment - Genqiang Su; Fen Li; Jingshuang Lin; Caifeng Liu; Gangrong Shi (Plant and Soil, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Ralstonia solanacearum nlpD (RSc1206) contributes to host adaptation - Chi-Yin Hsieh; Jaw-Fen Wang; Pei-Cheng Huang; Der-Kang Lu; Yu-Mei Lin; Wen-Chieh Yang; Chiu-Ping Cheng (European Journal of Plant Pathology, 2012)

NMDA receptor glycine modulatory site in the ventral tegmental area regulates the acquisition, retrieval, and reconsolidation of cocaine reward memory - Shuang-jiang Zhou; Li-fen Xue; Xue-yi Wang; Wen-gao Jiang; Yan-xue Xue; Jian-feng Liu; Yin-yin He; Yi-xiao Luo; Lin Lu (Psychopharmacology, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Experimental study on the effect of waves on netting panels at a range of angles to the wave direction - Wei-hua Song; Zhen-lin Liang; Rong Wan; Fen-Fang Zhao; Kinoshita Takeshi; Liu-yi Huang; Jia-zhi Ma; Bo-hai Chen (Fisheries Science, 2012)

Transcriptional analysis and functional characterization of XCC1294 gene encoding a GGDEF domain protein in Xanthomonas campestris pv. campestris - Yi-Min Hsiao; Wan-Ling Song; Chao-Tsai Liao; I-Hsuan Lin; Mei-Ying Pan; Ching-Fen Lin (Archives of Microbiology, 2012)

Inhibitor of DNA-binding-1/inhibitor of differentiation-1 (ID-1) is implicated in various aspects of gastric cancer cell biology - Wei Li; Chun-Hua Zhang; Yi-Lin Hong; Jun Li; Yong-Mei Hu; Cui-Fen Zhao (Molecular Biology Reports, 2012)

Role of interleukin 1 beta in esophageal squamous cell carcinoma - Miao-Fen Chen; Ming-Shian Lu; Ping-Tsung Chen; Wen-Cheng Chen; Paul-Yang Lin; Kuan-Der Lee (Journal of Molecular Medicine, 2012)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

Implementation of a Fast-Track Clinical Pathway Decreases Postoperative Length of Stay and Hospital Charges for Liver Resection - De-Xin Lin; Xuan Li; Qi-Wen Ye; Fen Lin; Lin-Li Li; Qi-Yu Zhang (Cell Biochemistry and Biophysics, 2011)

Biophysical studies of an NAD(P)+-dependent aldehyde dehydrogenase from Bacillus licheniformis - Huei-Fen Lo; Jian-Yu Su; Hsiang-Ling Chen; Jui-Chang Chen; Long-Liu Lin (European Biophysics Journal, 2011)

Assessing growing season beginning and end dates and their relation to climate in Taiwan using satellite data - Chung-Te Chang; Teng-Chiu Lin; Su-Fen Wang; Matthew A. Vadeboncoeur (International Journal of Remote Sensing, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Retrieval of chlorophyll a concentration from a fluorescence enveloped area using hyperspectral data - Fen-Fen Liu; Chu-Qun Chen; Shi-Lin Tang; Da-Zhao Liu (International Journal of Remote Sensing, 2011)

HLA polymorphism of the Zhuang population reflects the common HLA characteristics among Zhuang-Dong language-speaking populations - Li Shi; Xiao-qin Huang; Lei Shi; Yu-fen Tao; Yu-feng Yao; Liang Yu; Ke-qin Lin; Wen Yi; Hao Sun; Katsushi Tokunaga; Jia-you Chu (Journal of Zhejiang University-SCIENCE B, 2011)

A comparative study on arsenic and humic substances in alluvial aquifers of Bengal delta plain (NW Bangladesh), Chianan plain (SW Taiwan) and Lanyang plain (NE Taiwan): implication of arsenic mobilization mechanisms - A. H. M. Selim Reza; Jiin-Shuh Jean; Huai-Jen Yang; Ming-Kuo Lee; Hua-Fen Hsu; Chia-Chuan Liu; Yao-Chang Lee; Jochen Bundschuh; Kao-Hong Lin; Chi-Yu Lee (Environmental Geochemistry and Health, 2011)

Traceless synthesis of diketopiperazine fused tetrahydro-β-carbolines on soluble polymer support - Kaushik Chanda; Cheng-Ting Chou; Jin-Ji Lai; Shu-Fen Lin; Gorakh S. Yellol; Chung-Ming Sun (Molecular Diversity, 2011)

Fast Cleanup System Combined with a Dioxin-responsive Element-driven Luciferase Bioassay for Analysis of Polychlorinated Dibenzo-p-dioxins/furans in Sediments and Soils - How-Ran Chao; Ya-Fen Wang; Ding-Yan Lin; Yi-Ting Cheng; Tsui-Chun Tsou (Bulletin of Environmental Contamination and Toxicology, 2011)

Effects of Tai Chi on adiponectin and glucose homeostasis in individuals with cardiovascular risk factors - Rei-Yeuh Chang; Malcolm Koo; Meng-Ying Ho; Zi-Zi Lin; Zer-Ran Yu; Yen-Fen Lin; Be-Jen Wang (European Journal of Applied Physiology, 2011)

Determination of Ozonization Reaction Rate Constants of Aromatic Pollutants and QSAR Study - Jian Lin Jiang; Xiang An Yue; Qiu Fen Chen; Zhen Gao (Bulletin of Environmental Contamination and Toxicology, 2010)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Human herpesvirus 8 viral FLICE-inhibitory protein retards cell proliferation via downregulation of Id2 and Id3 expression - Yi-Fen Wang; Lin-Yu Wang; Yi-Ling Li; Huey-Wen Shyu; Yee-Hsuan Chiou; Miao-Chen Chou; Kuan-Hua Lin; Ming-Hong Tai; Chang-Yu Chen (Molecular and Cellular Biochemistry, 2010)

Erratum to: AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

The envelope glycoprotein domain III of dengue virus type 2 induced the expression of anticoagulant molecules in endothelial cells - Lien-Cheng Chen; Trai-Ming Yeh; Yi-Ying Lin; Yi-Fen Wang; Shu-Jem Su; Chang-Yu Chen; Kuan-Hua Lin; Miao-Chen Chou; Huey-Wen Shyu (Molecular and Cellular Biochemistry, 2010)

Effect of the C-terminal domains and terminal residues of catalytic domain on enzymatic activity and thermostability of lichenase from Clostridium thermocellum - Dong Niu; Xu-xia Zhou; Tao-yan Yuan; Zhi-wei Lin; Hui Ruan; Wei-fen Li (Biotechnology Letters, 2010)

Probing the catalytically essential residues of a recombinant dipeptidyl carboxypeptidase from Escherichia coli - Huei-Fen Lo; Hsiang-Ling Chen; Shao-Yu Yen; Ping-Lin Ong; Wen-Shiue Chang; Chen-Tien Chang (Biologia, 2010)

AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Morphologic observation and classification criteria of atretic follicles in guinea pigs - Wei Wang; Hong-lin Liu; Wei Tian; Fen-fen Zhang; Yan Gong; Jin-wei Chen; Da-gan Mao; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2010)

Identification and characterization of the Enterobacter complex causing mulberry (Morus alba) wilt disease in China - Guo-Fen Wang; Guan-Lin Xie; Bo Zhu; Jun-Sheng Huang; Bo Liu; Praphat Kawicha; Lesley Benyon; Yong-Ping Duan (European Journal of Plant Pathology, 2010)

Dynamics of Carbendazim Residue in Panax notoginseng and Soil - Jialun Wu; Houdao Wei; Xiaofei Sui; Jian Lin; Tianyu Wang; Guangquan Fen; Jian Xue (Bulletin of Environmental Contamination and Toxicology, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Effects of the multiple polyadenylation signal AAUAAA on mRNA 3′-end formation and gene expression - Hsin-Hung Lin; Li-Fen Huang; Hsiao-Chien Su; Shih-Tong Jeng (Planta, 2009)

Tandem organization of StarkB element (22.8 kb) in the maize B chromosome - Kuan-lin Lo; Shu-fen Peng; Liang-jwu Chen; Bor-yaw Lin (Molecular Genetics and Genomics, 2009)

Prediction of interaction between small molecule and enzyme using AdaBoost - Bing Niu; Yuhuan Jin; Lin Lu; Kaiyan Fen; Lei Gu; Zhisong He; Wencong Lu; Yixue Li; Yudong Cai (Molecular Diversity, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

Detection of race 1 strains of Ralstonia solanacearum in field samples in Taiwan using a BIO-PCR method - Chih-Hung Lin; Shih-Tien Hsu; Kuo-Ching Tzeng; Jaw-Fen Wang (European Journal of Plant Pathology, 2009)

Expression and purification of Zantedeschia aethiopica agglutinin in Escherichia coli - Ling Lin; Xue-Fen Liu; Ling-Chuan Hu; Yin Zhou; Xiao-Fen Sun; Ke-Xuan Tang (Molecular Biology Reports, 2009)

The predictive role of E2-EPF ubiquitin carrier protein in esophageal squamous cell carcinoma - Miao-Fen Chen; Kuan-Der Lee; Ming-Shian Lu; Chih-Cheng Chen; Ming-Ju Hsieh; Yun-Hen Liu; Paul-Yang Lin; Wen-Cheng Chen (Journal of Molecular Medicine, 2009)

The dipeptidyl carboxypeptidase of Escherichia coli novablue: overproduction and molecular characterization of the recombinant enzyme - Hsiang-Ling Chen; Chen-Tien Chang; Long-Liu Lin; Tein-Yu Li; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2009)

Influence of N-Terminal Truncations on the Functional Expression of Bacillus licheniformis γ-Glutamyltranspeptidase in Recombinant Escherichia coli - Long-Liu Lin; Li-Yu Yang; Hui-Yu Hu; Huei-Fen Lo (Current Microbiology, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Glutamic acid 219 is critical for the thermostability of a truncated α-amylase from alkaliphilic and thermophilic Bacillus sp. strain TS-23 - Long-Liu Lin; Jai-Shin Liu; Wen-Ching Wang; Szu-Han Chen; Chih-Chen Huang; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Bioavailability Effect of Methylprednisolone by Polymeric Micelles - Ching-Lin Chen; Shwu-Fen Chang; Daniel Lee; Lang-Yo Yang; Yi-Hsuan Lee; Chung Y. Hsu; Shwu-Jiuan Lin; Jiahorng Liaw (Pharmaceutical Research, 2008)

Characterization of a novel T4-type Stenotrophomonas maltophilia virulent phage Smp14 - Chiy-Rong Chen; Ching-Hsuan Lin; Juey-Wen Lin; Chi-I Chang; Yi-Hsiung Tseng; Shu-Fen Weng (Archives of Microbiology, 2007)

Protection effect of piper betel leaf extract against carbon tetrachloride-induced liver fibrosis in rats - Shun-Chieh Young; Chau-Jong Wang; Jing-Jing Lin; Pei-Ling Peng; Jui-Ling Hsu; Fen-Pi Chou (Archives of Toxicology, 2007)

A palynological study of environmental changes and their implication for prehistoric settlement in the Ilan Plain, northeastern Taiwan - Shu-Fen Lin; Tseng-Chieng Huang; Ping-Mei Liew; Su-Hwa Chen (Vegetation History and Archaeobotany, 2006)

Identifying the Scale Thresholds for Field-Data Extrapolation via Spatial Analysis of Landscape Gradients - Chi-Ru Chang; Pei-Fen Lee; Mei-Ling Bai; Tzer-Ton Lin (Ecosystems, 2006)

Gaseous nitrogen oxide repressed benzo[a]pyrene-induced human lung fibroblast cell apoptosis via inhibiting JNK1 signals - Jing-Hsien Chen; Fen-Pi Chou; Hui-Hsuan Lin; Chau-Jong Wang (Archives of Toxicology, 2005)

Evolution of the Euphrasia transmorrisonensis complex (Orobanchaceae) in alpine areas of Taiwan - Ming‐Jou Wu; Shing‐Fan Huang; Tseng‐Chieng Huang; Pei‐Fen Lee; Tsan‐Piao Lin (Journal of Biogeography, 2005)
Aims To unravel isolation and differentiation of the genetic structure of the Euphrasia transmorrisonensis complex, a showy herb, among alpine regions of mountain peaks in subtropical Taiwan and to infer its evolutionary history. Location Alpine ecosystems of high‐montane regions of Taiwan. Methods Phylogenetic analyses of the trn L intron and the trn L– trn F intergenic spacer of chloroplast (cp) DNA, and the intertranscribed spacer (ITS) of nuclear ribosomal (nr) DNA between 18S and 26S were carried out on 18 populations of the E. transmorrisonensis complex in Taiwan. Results In total, 10 haplotypes for cpDNA and 14 haplotypes for nrDNA were detected. Three population groups located in the northern, north‐eastern, and south‐central regions of the Central Mountain Range (CMR) were revealed according to the frequencies of haplotypes and haplotype lineages of nrDNA. Balancing selection might have played a role in the evolution of Euphrasia in Taiwan. Main conclusions By integrating the spatial‐genetic patterns of cpDNA and nrDNA, two possible evolutionary histories of Euphrasia in Taiwan were inferred. The favourable hypotheses for interpreting the data suggest at least three origins of the E. transmorrisonensis complex in Taiwan, corresponding to each nuclear lineage in the northern (II), northern/north‐eastern (I), and central/southern regions (III) with subsequent hybridization between lineages I and II and lineages II and III. These lineage boundaries are strengthened by the finding that haplotypes of C derived from cpDNA were found in the geographical region of lineage II of nrDNA, while haplotypes of A derived from cpDNA were found in the region of lineage III of nrDNA. Thus, the origin of chloroplasts exclusive to lineages II and III supports their long‐term isolation from one another.

Role of withdrawal in reinstatement of morphine-conditioned place preference - Lin Lu; Hai Chen; Wenjuan Su; Xin Ge; Wen Yue; Fen Su; Lan Ma (Psychopharmacology, 2005)

Adsorption-elution purification of chimeric Bacillus stearothermophilus leucine aminopeptidase II with raw-starch-binding activity - Yu-Wen Hua; Meng-Chun Chi; Huei-Fen Lo; Lih-Ying Kuo; Kuo-Lung Ku; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Energy flux, body size and density in relation to bird species richness along an elevational gradient in Taiwan - Tzung‐Su Ding; Hsiao‐Wei Yuan; Shu Geng; Yao‐Sung Lin; Pei‐Fen Lee (Global Ecology and Biogeography, 2005)
Aim To examine the species richness of breeding birds along a local elevational gradient and to test the following assumptions of the energy limitation hypothesis: (1) the energy flux through birds is positively correlated with above‐ground net primary productivity, (2) bird density is positively correlated with total energy flux, and (3) bird species richness is positively correlated with bird density. Location An elevational gradient from 1400 to 3700 m on Mt. Yushan, the highest mountain in Taiwan (23°28′30″ N, 120°54′00″ E), with a peak of 3952 m a.s.l. Methods We established 50 sampling stations along the elevational gradient. From March to July 1992, we estimated the density of each bird species using the variable circular‐plot method. Above‐ground net primary productivity was modelled using monthly averages from weather data for the years 1961–90. Results Bird species richness had a hump‐shaped relationship with elevation and with net primary productivity. Bird energy flux was positively correlated with net primary productivity and bird species richness was positively correlated with bird density. The relationship between bird density and energy flux was hump‐shaped, which does not support one assumption of the energy limitation hypothesis. Main conclusions The results supported two essential assumptions of the energy limitation hypothesis. However, when energy availability exceeded a certain level, it could decrease species richness by increasing individual energy consumption, which reduced bird density. Thus, energy availability is a primary factor influencing bird species richness at this scale, but other factors, such as body size, could also play important roles.

Stabilization of a truncated Bacillus sp. strain TS-23 α-amylase by replacing histidine-436 with aspartate - Huei-Fen Lo; Ya-Hui Chen; Nai-Wan Hsiao; Hsiang-Ling Chen; Hui-Yu Hu; Wen-Hwei Hsu; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Conservation of the horseshoe crab at Kinmen, Taiwan: strategies and practices - Chang-Po Chen; Hsin-Yi Yeh; Po-Fen Lin (Biodiversity and Conservation, 2004)

Site-Directed Mutagenesis of the Conserved Threonine, Tryptophan, and Lysine Residues in the Starch-Binding Domain of Bacillus sp. Strain TS-23 a-Amylase - Huei-Fen Lo; Wen-Ying Chiang; Meng-Chun Chi; Hui-Yu Hu; Long-Liu Lin (Current Microbiology, 2004)

The tumorigenic characteristics of Lime-Piper betel quid-transformed JB6 cells - Ming-Hsun Lin; Chau-Jong Wang; Hui-Pei Huang; Ming-Yung Chou; Fen-Pi Chou (Archives of Toxicology, 2004)

Identification of essential histidine residues in a recombinant ?-amylase of thermophilic and alkaliphilic Bacillus sp. strain TS-23 - Chen-Tien Chang; Huei-Fen Lo; Meng-Chun Chi; Chia-Yu Yao; Wen-Hwei Hsu; Long-Liu Lin (Extremophiles, 2003)

Replacement of Methionine 208 in a Truncated Bacillus sp. TS-23 α-Amylase with Oxidation-Resistant Leucine Enhances Its Resistance to Hydrogen Peroxide - Long-Liu Lin; Huei-Fen Lo; Wen-Ying Chiang; Hui-Yu Hu; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2003)

Nickel-induced oxidative stress and effect of antioxidants in human lymphocytes - Chang-Yu Chen; Yi-Fen Wang; Yu-Hwan Lin; Shu-Fang Yen (Archives of Toxicology, 2003)

Deletion analysis of the C-terminal region of the α-amylase of Bacillus sp. strain TS-23 - Huei-Fen Lo; Long-Liu Lin; Wen-Ying Chiang; Meng-Chun Chie; Wen-Hwei Hsu; Chen-Tien Chang (Archives of Microbiology, 2002)

Characterization of stress-responsive genes, hrcA-grpE-dnaK-dnaJ , from phytopathogenic Xanthomonas campestris - Shu-Fen Weng; Pan-Ming Tai; Cheng-Hwa Yang; Cheng-Der Wu; Wan-Ju Tsai; Juey-Wen Lin; Yi-Hsiung Tseng (Archives of Microbiology, 2001)

The N-Terminal Signal Sequence and the Last 98 Amino Acids Are Not Essential for the Secretion of Bacillus sp. TS-23 α-Amylase in Escherichia coli - Huei-Fen Lo; Long-Liu Lin; Chien-Cheng Li; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2001)

Identification of Essential Cysteine Residues in 3-Deoxy-d-Arabino-Heptulosonate-7-Phosphate Synthase from Corynebacterium glutamicum - Long-Liu Lin; Hui-Fen Liao; Hungchien Roger Chien; Wen-Hwei Hsu (Current Microbiology, 2001)

Expression of receptor protein tyrosine phosphatase agr; mRNA in human prostate cancer cell lines - Stanislav Zelivianski; Jeanenne Dean; Deepak Madhavan; Fen-Fen Lin; Ming-Fong Lin (Molecular and Cellular Biochemistry, 2000)

Lipid peroxidation in liver of rats administrated with methyl mercuric chloride - Te-Hsien Lin; Yeou-Lih Huang; Su-Fen Huang (Biological Trace Element Research, 1996)